Independent academic Data Monitoring Committees for clinical trials in cardiovascular and cardiometabolic diseases. (8th March 2017) - Filippatos, Gerasimos S.; de Graeff, Pieter; Bax, Jeroen J.; Borg, John‐Joseph; Cleland, John G.F.; Dargie, Henry J.; Flather, Marcus; Ford, Ian; Friede, Tim; Greenberg, Barry; Henon‐Goburdhun, Cécile; Holcomb, Richard; et al.
Abstract: Data Monitoring Committees (DMCs) play a crucial role in the conducting of clinical trials to ensure the safety of study participants and to maintain a trial's scientific integrity. Generally accepted standards exist for DMC composition and operational conduct. However, some relevant issues are not specifically addressed in current guidance documents, resulting in uncertainties regarding optimal approaches for communication between the DMC, steering committee, and sponsors, release of information, and liability protection for DMC members. The Heart Failure Association (HFA) of the European Society of Cardiology (ESC), in collaboration with the Clinical Trials Unit of the European Heart Agency (EHA) of the ESC convened a meeting of international experts in DMCs for cardiovascular and cardiometabolic clinical trials to identify specific issues and develop steps to resolve challenges faced by DMCs.The main recommendations from the meeting relate to methodological consistency, independence, managing conflicts of interest, liability protection, and training of future DMC members. This paper summarizes the key outcomes from this expert meeting, and describes the core set of activities that might be further developed and ultimately implemented by the ESC, HFA, and other interested ESC constituent bodies. The HFA will continue to work with stakeholders in cardiovascular and cardiometabolic clinical research to promote these goals.